Rocky road - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
Frank and Joe try to stop someone from destroying Niagara Falls.
008-012.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Detective and mystery stories; Niagara Falls (N.Y. and Ont.) -- Juvenile literature